Study of regional-scale boundary layer characteristics over Northern India with a special reference to the role of the Thar Desert in regional-scale transport - Maithili Sharan. (2011)
A nomogram was prepared by [Golder, 1972. Boundary Layer Meteorology 3, 47–58] to compute the surface layer